Karakteristik dan Kepribadian Seorang Wirausaha - Isti koma; Sodikin Sodikin; Rahma Wulandari; Amelia handayani; Martoyo Martoyo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The characteristics and character of an entrepreneur play a significant role in the success of the business being run. Entrepreneurs often have traits such as courage, creativity, and intensity that allow them to experience various challenges in the business world. Not only that, the ability to take calculated risks and adapt to market changes is also a key aspect in their expedition as entrepreneurs. This trait not only influences business decisions but also contributes to their individual and professional growth. Entrepreneurial character is often indicated by an orientation towards achievement and great internal motivation. They tend to have a clear vision and are able to formulate long-term goals for their business. Not only that, the ability to build networks and establish good relationships with various parties, such as customers, partners, and employees, is also an important aspect of an entrepreneur's character. This helps them in generating new opportunities and maintaining business continuity. In the context of economic growth, a description of the characteristics and character of entrepreneurs is very important for encouraging innovation and business development. By identifying these traits, aspiring entrepreneurs can improve themselves and better prepare themselves to face the challenges that exist. In addition, support from areas such as learning and training can also help hone the personality and character needed to succeed in the world of entrepreneurship.